2009
DOI: 10.1371/journal.pone.0004897
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering von Hippel-Lindau (VHL/Vhl)-Associated Pancreatic Manifestations by Inactivating Vhl in Specific Pancreatic Cell Populations

Abstract: The von Hippel-Lindau (VHL) syndrome is a pleomorphic familial disease characterized by the development of highly vascularized tumors, such as hemangioblastomas of the central nervous system, pheochromocytomas, renal cell carcinomas, cysts and neuroendocrine tumors of the pancreas. Up to 75% of VHL patients are affected by VHL-associated pancreatic lesions; however, very few reports in the published literature have described the cellular origins and biological roles of VHL in the pancreas. Since homozygous los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 48 publications
3
40
1
Order By: Relevance
“…In view of abundant evidence linking certain types of cysts to defects in primary cilia, it has been suggested that the microtubule stabilization function of VHL is key to its role in suppressing cysts (66). Several mouse models in which the VHL gene has been inactivated develop various cysts (although not SCAs) (67)(68)(69)(70), suggesting fertile avenues for future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In view of abundant evidence linking certain types of cysts to defects in primary cilia, it has been suggested that the microtubule stabilization function of VHL is key to its role in suppressing cysts (66). Several mouse models in which the VHL gene has been inactivated develop various cysts (although not SCAs) (67)(68)(69)(70), suggesting fertile avenues for future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…39 In our studies, the b-cell-specific VHL-knockout mice, in which cre-mediated VHL deletion was under the control of the RIP, did not demonstrate any evidence of tumor development, similar to a study by Cantley et al 27 In addition, in this study, mice in which VHL was deleted under the control of the Pdx-1 promoter (Tg (Pdx1-cre) 1Herr) was used, which also demonstrated a glucose intolerant phenotype due to impaired insulin secretion. However, another study by Shen et al 40 showed that mice with Pdx-1-driven VHL deletion in a different genetic background (Tg (Pdx1-cre) 89.1Dam) resulted in tumor development and early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Global homozygous deletion of Vhl in mice results in embryonic death; global heterozygous Vhl deletion, meanwhile, is not associated with any significant abnormalities even at 15 months (Gnarra et al, 1997). Furthermore, β or α cell-specific homozygous Vhl deletion in mice also does not results in PNETs (Shen et al, 2009b). Specific homozygous Vhl deletion from M A N U S C R I P T…”
Section: Vhl Deletionmentioning
confidence: 99%